Die naamgewing van die dorp Pierre van Ryneveld (Van Ryneveldpark) en sy uitbreidings - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
Pierre van Ryneveld was born at Senekal OFS on 2.5.1891. Part of his schooling took place at Grey College, Bloemfontein. After obtaining a BSc at the Imperial College in London he enlisted as a cadet in the London Officers Training Corps in 1914 and became a Flight Officer in the illustrious Royal Flying Corps in 1915. At the end of World War I he was a Colonel in the RAF. In 1920 he was summoned by General J.C. Smuts to "start the Air Force in South Africa" and was consequently regarded as the ’father’ of the SAAF. Gen, Sir (as he later became) Pierre van Ryneveld became a legend in his lifetime and this article describes how he and other military figures were honoured by the establishment of Van Ryneveld Park.